Optimizing Standardization Systems and Standardizing Clinical Practice: Interpretation of Quality Standards for Medical 68Ge/68Ga Generators and 68Ga Radiopharmaceuticals and Quality Standards for Medical 177Lu and Its Radiopharmaceuticals - LAI Yuxin; PENG Yumeng; WANG Guochang (Xiehe Yixue Zazhi)
On January 1, 2022, the China International Association for the Promotion of Science and Technology (CIAPST) officially implemented two pivotal standards: Quality Standards for Medical Germanium-68/Gallium-68 (68Ge/68Ga) Generators and Gallium-68 Radiopharmaceuticals (T/CI 046-2021) and Quality Standards for Medical Lutetium-177 (177Lu) and Its Radiopharmaceuticals(T/CI 047-2021). These standardsintroduce innovative requirements for quality control and clinical application of radiopharmaceuticals, marking a significant advancement in China's regulatory framework for nuclear medicine.This article provides a comprehensive analysis of the technical rationale, QC protocols, and clinical implications outlined in the standards. Against the backdrop of China's evolving nuclear medicine landscape, we further identify challenges in implementation (e.g., production consistency, regulatory compliance) and propose actionable strategies to optimize radiopharmaceutical quality management systems. Our perspective aims to support the standardization and global integration of China's radiopharmaceutical industry.